Fresh takes on teaching literary elements : how to teach what really matters about character, setting, point of view and theme - Wilhelm, Jeffrey D., 1959-; Wilhelm, Jeffrey D., 1959-; National Council of Teachers of English (New York : Scholastic ; Urbana, IL : NCTE, 2010)
Offers tools and strategies for teaching literary elements to middle and high school students, covering character, theme, point of view, and setting, and including activities.
"Grades 6-12"--Cover.
Includes bibliographical references (p. 203-208).
Professional
Professional
Keywords: Character in literature; Language arts (Secondary) -- United States; Literature, Comparative -- Themes, motives; Literature -- Study and teaching (Secondary); Setting (Literature); Character in literature; Comparative literature; Language arts; Literature; Literature -- Study and teaching